2001
DOI: 10.1128/aem.67.12.5656-5667.2001
|View full text |Cite
|
Sign up to set email alerts
|

Percent G+C Profiling Accurately Reveals Diet-Related Differences in the Gastrointestinal Microbial Community of Broiler Chickens

Abstract: Broiler chickens from eight commercial farms in Southern Finland were analyzed for the structure of their gastrointestinal microbial community by a nonselective DNA-based method, percent G؉C-based profiling. The bacteriological impact of the feed source and in-farm whole-wheat amendment of the diet was assessed by percent G؉C profiling. Also, a phylogenetic 16S rRNA gene (rDNA)-based study was carried out to aid in interpretation of the percent G؉C profiles. This survey showed that most of the 16S rDNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 37 publications
5
87
0
5
Order By: Relevance
“…The isolated bacteria were then lysed and DNA was purified by a protocol comprising enzymatic, chemical and physical steps as described elsewhere in detail (Apajalahti et al, 1998(Apajalahti et al, , 2001. The DNA was fractionated by 72 h CsCl equilibrium density gradient centrifugation, which fractionates chromosomes of the component taxa, based on their characteristic G þ C content as described previously (Apajalahti et al, 1998(Apajalahti et al, , 2001Holben et al, 2004). This separation is based on differential density imposed by the AT-dependent DNA-binding dye bis-benzimidazole.…”
Section: Patient Cohortmentioning
confidence: 99%
“…The isolated bacteria were then lysed and DNA was purified by a protocol comprising enzymatic, chemical and physical steps as described elsewhere in detail (Apajalahti et al, 1998(Apajalahti et al, , 2001. The DNA was fractionated by 72 h CsCl equilibrium density gradient centrifugation, which fractionates chromosomes of the component taxa, based on their characteristic G þ C content as described previously (Apajalahti et al, 1998(Apajalahti et al, , 2001Holben et al, 2004). This separation is based on differential density imposed by the AT-dependent DNA-binding dye bis-benzimidazole.…”
Section: Patient Cohortmentioning
confidence: 99%
“…Major factors affecting microbial number and composition along the length of the intestine appear to be age, diet, and host genotype (van der Wielen et al, 2000;Apajalahti et al, 2001;Hill et al, 2005). Comparisons between the zoo animals described previously revealed that diet was the strongest determining factor in shaping microbial composition, where animals were grouped based on whether they were carnivores, herbivores, or omnivores.…”
Section: Factors Affecting the Gut Microbiomementioning
confidence: 99%
“…Staining for cytoplasmic inclusions and chemical analysis for storage polysaccharide and poly-b-hydroxybutyrate were carried out as described by Hanson & Phillips (1981). The G+C content was determined by means of the differential dyebinding method of Apajalahti et al (2001), using regression analysis (r 2 >0?99) of data obtained from gradients containing standard DNA samples of known G+C content (Clostridium perfringens, Escherichia coli and 'Micrococcus lysodeikticus'). Sample DNA was analysed in triplicate.…”
Section: Bacterial Identificationmentioning
confidence: 99%